2000
DOI: 10.1108/07363760010349920
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in information search strategies for a Christmas gift

Abstract: Examines the underlying determinants of in‐store information search for a Christmas clothing gift, specifically focusing on gender differences. Two non‐personal (general and specific) and one personal (sales clerk assistance) in‐store information search domains were obtained from the results of a survey of actual consumers carried out shortly after the Christmas season. Consistent with the predictions of the selectivity model, females appeared to comprehensively acquire in‐store information, whereas males appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(122 citation statements)
references
References 52 publications
6
104
1
4
Order By: Relevance
“…These differences support the findings that men are characteristically functional, impulsive shoppers while women are typically hedonic, organized shoppers (Hu & Jasper, 2004;Men buy, women shop, 2007;Wiedmann, Walsh, & Mitchell, 2001). Males report being confused by overchoice (Bakewell & Mitchell, 2004;Cleveland et al, 2003), while females conduct more product search and product/price comparisons (Cleveland et al, 2003;Dennis & McCall, 2005;Laroche, Saad, Cleveland, & Browne, 2000). Men often purchase well-known brands to reduce confusion brought on by overchoice and are less focused on promotions than women (Neff, 2011;Wiedmann et al, 2001); however, Brosdahl & Carpenter (2011) found male participants to be price conscious and brand loyal.…”
Section: Gendersupporting
confidence: 73%
“…These differences support the findings that men are characteristically functional, impulsive shoppers while women are typically hedonic, organized shoppers (Hu & Jasper, 2004;Men buy, women shop, 2007;Wiedmann, Walsh, & Mitchell, 2001). Males report being confused by overchoice (Bakewell & Mitchell, 2004;Cleveland et al, 2003), while females conduct more product search and product/price comparisons (Cleveland et al, 2003;Dennis & McCall, 2005;Laroche, Saad, Cleveland, & Browne, 2000). Men often purchase well-known brands to reduce confusion brought on by overchoice and are less focused on promotions than women (Neff, 2011;Wiedmann et al, 2001); however, Brosdahl & Carpenter (2011) found male participants to be price conscious and brand loyal.…”
Section: Gendersupporting
confidence: 73%
“…The ads used in Darley and Smith's (1995) study were about 'female' products such as weighing scales and electric blankets, possibly causing men to feel less interested-which in turn may have led them to process the information less comprehensively. Similarly, the results from the Laroche et al (2000) study show that "Shopping is still an activity in which the female plays a dominant role" (p. 504), suggesting that men might use heuristic cues when shopping for a gift because they are not interested in shopping itself. Thus, it may be that the reported differences can be at least in part attributed to gender differences in interests rather than to gender differences in information processing.…”
Section: Introductionmentioning
confidence: 85%
“…For example, a study by Laroche, Saad, Cleveland, and Browne (2000) showed that when shopping for a gift, women's information search process was more systematic and comprehensive than men's. Men on the other hand tended to rely more on heuristic strategies-such as relying on brand names and product price, or directly consulting a sales clerk to quickly obtain what was needed.…”
Section: Introductionmentioning
confidence: 99%
“…Rocha et al (2005) had also experienced different requirements for clothing and fashion products based upon age and gender. Laroche et al (2000) had found gender differences in relation to acquisition of in-store information for buying Christmas clothing gifts. Vankatesh and Morris (2000) studied the moderating role of gender in the adoption of a new software system.…”
Section: Literature Reviewmentioning
confidence: 99%